2017
DOI: 10.1038/srep42473
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases (MAPKs) regulate IL-6 over-production during concomitant influenza virus and Staphylococcus aureus infection

Abstract: Bacterial super-infections are a major complication of influenza virus (IV) infections and often lead to severe pneumonia. One hallmark of IV-associated Staphylococcus aureus (S. aureus) infection is rapid progression to a serious disease outcome. Changes in immune and inflammatory host responses increase morbidity and complicate efficient therapy. A key player during inflammation is the multifunctional cytokine IL-6. Although increased IL-6 levels have been observed after severe disease upon IV and/or bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 62 publications
(110 reference statements)
3
24
0
Order By: Relevance
“…MAPKs are known to regulate TNF production via p-c-jun in other inflammation models (50). Here, it was observed that the expression of p-c-jun is dependent on p-JNK pathway (as SP reduces p-c-jun expression in a dose dependent manner), whereas induction of p-IRF3 is dependent on both MAPKs (p38 and JNK) during CHIKV infection in macrophages.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…MAPKs are known to regulate TNF production via p-c-jun in other inflammation models (50). Here, it was observed that the expression of p-c-jun is dependent on p-JNK pathway (as SP reduces p-c-jun expression in a dose dependent manner), whereas induction of p-IRF3 is dependent on both MAPKs (p38 and JNK) during CHIKV infection in macrophages.…”
Section: Discussionmentioning
confidence: 82%
“…Pharmaceutical Inhibitors Specific to p-p38 and p-JNK Reduces CHIKV Induced TNF Production in the Host Macrophages Activation of MAPKs by different pathogens has been shown to induce pro-inflammatory cytokines such as TNF in the host cells (50,54). Since, CHIKV triggers robust TNF production (a key mediator of inflammation) in the host macrophages (31,37), it was interesting to investigate whether any MAPKs are involved in this pathway.…”
Section: Sb203580 Treatment Reduces Chikv Infection In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…To further confirm the involvement of FFAR3 signalling, HLFs were release, we used protein immunoblotting to investigate the activation of signalling pathways. We focussed on five known major signalling pathways (NF-κB, p38 MAPK, AKT, ERK and SAPK/JNK), all of which have been shown to stimulate IL-6 and/or CXCL8 production (22,26,36,41). Phosphorylation of NF-κB was increased 30 minutes after stimulation with TNFα alone (n = 10, p<0.01), but was not increased by concomitant treatment with propionate (p<0.01) ( Figure 4A).…”
Section: Scfas Enhance Tnfα-induced Il-6 and Cxcl8 Release Through Ffmentioning
confidence: 99%